Pterygium – current review on pathogenesis and treatment - Jawor, Marcin; Wyględowska-Promieńska, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
A pterygium is a pinkish, triangular-shaped lump of fibrovascular tissue that grows from the conjunctiva on to the cornea. Pterygium is usually bilateral, located within the nasal aspect of the conjunctiva. Most lesions grow slowly over an individual’s lifetime, while some stop growing after a certain point. UV radiation (usually from sunlight) is the most common risk factor for pterygium. Other, less common causal factors include chronic ocular irritation, conjunctival dryness and exposure to dry, dusty environments. The management depends on the stage of pterygium and ranges from watchful waiting to diverse surgical interventions in more severe cases. The outcomes are uncertain and changeable.